New nucleopolyhedrovirus isolate in the management of Spodoptera eridania - ALIXELHE P. DAMASCENA; FERNANDO Z. MADALON; LUIS M. DE ARAUJO JUNIOR; DIRCEU PRATISSOLI; CARLOS EDUARDO C. PAIVA; LORENA C. MACHADO; HUGO GONÇALVES JUNIOR; VINÍCIUS H. BELLO (Anais da Academia Brasileira de Ciências)
Abstract Spodoptera eridania is considered a polyphagous pest, as it attacks several crops. The aim of this study was to identify a virus isolate present in symptomatic S. eridania caterpillars. The virus sample was extracted and OBs purification performed. Viral DNA was extracted using the PureLink Viral RNA/DNA Mini Kit (ThermoFisher) and primers prl8-1 and prl8-1B were used for amplification of the gene fragment. The isolate was identified showing high genetic similarity with the isolate “Spodoptera eridania nucleopolyhedrovirus isolate CNPSo-165”, characterizing itself as a novelty in the scenario and as promising, adding the tactics available for the integrated management of S. eridania.